Longitudinal assessment of the association between pesticide exposure and lifestyle with Parkinson’s disease motor severity - Theresa Lüth; Amke Caliebe; Carolin Gabbert; Sebastian Sendel; Björn-Hergen Laabs; Inke R. König; Christine Klein; Joanne Trinh (npj Parkinson's Disease)
Abstract Longitudinal investigations on the relationship between lifestyle exposures and motor severity are lacking. In this longitudinal study, we included patients with idiopathic Parkinson’s disease (iPD) (N = 5139) and LRRK2-related PD (N = 81) from PPMI-Online and Fox Insight. Motor aspects were followed for up to five years. We investigated the association between environmental exposure, lifestyle factors and motor aspect severity over time by applying linear mixed effects models. In LRRK2-PD, black tea consumption was associated with less severe motor aspects (β = −0.51, p = 0.028). In patients with iPD, pesticide exposure was associated with more severe motor aspects over time in PPMI-Online (β = 0.23, p = 3.56 × 10− 9). Lastly, caffeinated soda was associated with more severe motor aspects in patients with iPD from PPMI-Online (β = 0.15, p = 3.84 × 10−8) and Fox Insight (β = 0.09, p = 0.031). We suggest that pesticide exposure and lifestyle factors may affect motor severity in patients with LRRK2-PD and iPD, demonstrating the impact on patients even after disease onset.